2014
DOI: 10.1186/1471-2407-14-913
|View full text |Cite
|
Sign up to set email alerts
|

Independent overexpression of the subunits of translation elongation factor complex eEF1H in human lung cancer

Abstract: BackgroundThe constituents of stable multiprotein complexes are known to dissociate from the complex to play independent regulatory roles. The components of translation elongation complex eEF1H (eEF1A, eEF1Bα, eEF1Bβ, eEF1Bγ) were found overexpressed in different cancers. To gain the knowledge about novel cancer-related translational mechanisms we intended to reveal whether eEF1H exists as a single unit or independent subunits in different human cancers.MethodsThe changes in the expression level of every subun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…More than two-fold rise in the level of at least one eEF1B subunit was observed in 52% of 25 lung carcinoma samples. Again, the simultaneous increase in the level of all three eEF1B subunits was observed in one case, simultaneous upregulation of eEF1Bα and eEF1Bβ was also found in one case, simultaneous upregulation of eEF1Bβ and eEF1Bγ was observed in five cases while no correlated elevation of eEF1Bα and eEF1Bγ was found (Veremieva et al, 2014). The authors concluded that cancer-related upregulation of individual subunits rather than the whole eEF1B complex takes place in both cancers.…”
Section: Complex Mattermentioning
confidence: 93%
See 3 more Smart Citations
“…More than two-fold rise in the level of at least one eEF1B subunit was observed in 52% of 25 lung carcinoma samples. Again, the simultaneous increase in the level of all three eEF1B subunits was observed in one case, simultaneous upregulation of eEF1Bα and eEF1Bβ was also found in one case, simultaneous upregulation of eEF1Bβ and eEF1Bγ was observed in five cases while no correlated elevation of eEF1Bα and eEF1Bγ was found (Veremieva et al, 2014). The authors concluded that cancer-related upregulation of individual subunits rather than the whole eEF1B complex takes place in both cancers.…”
Section: Complex Mattermentioning
confidence: 93%
“…The levels of mRNA and a protein coded by this mRNA do not often correlate (Liu et al, 2016) which is valid for eEF1B subunits as well (Veremieva et al, 2011(Veremieva et al, , 2014Flores et al, 2016). This mini-review is focused on eEF1B proteins, therefore cancer-related changes in the levels of corresponding mRNAs are not considered here, although such changes may be of marker/prognostic importance (Hassan et al, 2018;Biterge-Sut, 2019).…”
Section: Eef1b Proteins In Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…For a long time the eEF1B complex was considered very stable, however, recently we have found that some pool of its subunits could exist separately from the complex in different human cancer tissues [1][2][3]. The role of non-complexed subunits remains elusive.…”
Section: Introductionmentioning
confidence: 99%